Bridging the literacy-performance gap: cognitive bias interaction and mentoring in MSMEs - Juliana Kadang; Djayani Nurdin; Munawarah Munawarah; Erwan S Farid; Surya Samudra; Effendi Lakada; Agus Firdaus (Manajemen dan Bisnis, 2026)
This study examines how financial literacy, cognitive biases, and behavior-based mentoring affect the performance of micro, small, and medium enterprises (MSMEs) in post-disaster Sigi, Central Sulawesi. The objectives were to assess relationships among financial literacy, cognitive bias, financial behavior, and business performance, and to evaluate the role of mentoring as an intervention. A mixed-methods design was used: a quantitative survey of 291 MSME actors who received mentoring, followed by in-depth qualitative interviews to enrich interpretation. Findings show that higher financial literacy promotes healthier financial practices and better business outcomes, while cognitive biases influence decisions in ways that can harm performance unless managed. Financial behavior operates as the key pathway linking knowledge and biases to performance. Mentoring improved practical financial practices but did not sufficiently alter underlying biases or strengthen the effect of literacy on behavior. Recommendations include redesigning mentoring to incorporate behavioral-economic debiasing, training mentors as behavioral coaches, and developing simple digital tools that prompt data-driven decisions to sustain improvements in MSME financial management.